A Hollow Argument: Understory Vegetation and Disturbance Determine Abundance of Hollow-Dependent Mammals in an Australian Tropical Savanna - Penton, Cara E.; Davies, Hugh F.; Radford, Ian J.; Woolley, Leigh-Ann; Rangers, Tiwi Land; Murphy, Brett P. (Frontiers in Ecology and Evolution, 2021)
Native mammals are suffering widespread and ongoing population declines across northern Australia. These declines are likely driven by multiple, interacting factors including altered fire regimes, predation by feral cats, and grazing by feral herbivores. In addition, the loss of tree hollows due to frequent, intense fires may also be contributing to the decline of hollow-dependent mammals. We currently have little understanding of how the availability of tree hollows influences populations of hollow-dependent mammals in northern Australian savannas. Here, we test the hypothesis that the abundance of hollow-dependent mammals is higher in areas with a greater availability of tree hollows. We used camera-trap data from 82 sites across the savannas of Melville Island, the largest island in monsoonal northern Australia. Royle–Nichols abundance-induced heterogeneity models were used to investigate the biophysical correlates of the abundance of three threatened mammals: northern brushtail possum (Trichosurus vulpecula arnhemensis), black-footed tree-rat (Mesembriomys gouldii), and brush-tailed rabbit-rat (Conilurus penicillatus). Our analyses included two variables that reflect the availability of tree hollows: the density of tree hollows, estimated from the ground, and the density of large eucalypt trees (Eucalyptus and Corymbia spp.). We found no evidence that the abundance of the three hollow-dependent mammals is positively associated with the availability of tree hollows on Melville Island. Despite their reliance on hollow-bearing trees for denning, the abundance of these mammals appears to be more strongly associated with other factors, such as the characteristics of the understory (i.e., shrub density), which affords protection from predators (including feral cats) and access to food resources. Future conservation management should aim to maintain a dense, diverse understory by managing fire and feral herbivores to facilitate the persistence of hollow-dependent mammals across northern Australia.